18q+, the progeny of a balanced translocation t(1;18)mat: case report with necropsy findings. - Hindi, A (1986)
A female infant with additional genetic material on the long arm of chromosome 18 is described. Cytogenetic studies of the infant and her mother showed that the altered region resulted from an unbalanced translocation of part of the long arm of chromosome 1. This chromosomal abnormality has not been reported previously, according to a recent registry of abnormal chromosome patterns. The patient had hydrops fetalis and multiple congenital abnormalities, involving the cardiovascular, respiratory, and skeletal systems, together with unusual facies. External features, radiological findings, and gross and microscopical examination at necropsy are presented and compared with previously reported cases of related but dissimilar chromosomal abnormalities.